Periodontal tray application of chlorine dioxide gel as an adjunct to scaling and root planing in the treatment of chronic periodontitis - Ira Komara; Edwin Alfa Winata; Agus Susanto; Ina Hendiani (Saudi Dental Journal)
Objective: Clinical improvement after periodontal tray application of chlorine dioxide gel as an adjunct to scaling and root planing (SRP) in the treatment of chronic periodontitis was studied for a period of 30 days. Materials and methods: The tray fabrication was performed in a dental laboratory using the Soft – Tray Sheets (Ultradent™), whereas scaling and root planing were done using ultrasonic scaler and hand instruments. A total of 36 subjects with chronic periodontitis were divided into 3 treatment groups: group I was treated with SRP procedure combined with the prescription-tray application of chlorine dioxide gel; group II was treated with SRP procedure with the application of chlorine dioxide alone; and group III was treated with SRP procedure alone. Clinical parameters examined were probing pocket depth (PPD) and papillary bleeding index (PBI); measurements were taken at baseline (day0) and 30 days after SRP (day 30). Comparison between treatment groups was tested statistically by Kruskal Wallis test and Analysis of Variance (ANOVA). Results: There were significant differences in the decrease of the average pocket depth and bleeding index in all the 3 treatment groups (P = 0.001). Decreases in the pocket depth of groups I, II, and III were 50.9%, 47.9%, and 27.8%, respectively. Decreases in the papillary bleeding index of groups I, II, and III were 88.2%, 68.9%, and 51.1%, respectively. Conclusion: The application of chlorine dioxide gel using the custom tray after SRP in the treatment of chronic periodontitis showed better clinical improvement in pocket depth reduction and bleeding index compared to SRP alone.